Moderating Effect of Cortical Thickness on BOLD Signal Variability Age-Related Changes - Pur, Daiana R.; Eagleson, Roy A.; de Ribaupierre, Anik; Mella, Nathalie; de Ribaupierre, Sandrine (Frontiers in Aging Neuroscience, 2019)
The time course of neuroanatomical structural and functional measures across the lifespan is commonly reported in association with aging. Blood oxygen-level dependent signal variability, estimated using the standard deviation of the signal, or “BOLD SD,” is an emerging metric of variability in neural processing, and has been shown to be positively correlated with cognitive flexibility. Generally, BOLD SD is reported to decrease with aging, and is thought to reflect age-related cognitive decline. Additionally, it is well established that normative aging is associated with structural changes in brain regions, and that these predict functional decline in various cognitive domains. Nevertheless, the interaction between alterations in cortical morphology and BOLD SD changes has not been modeled quantitatively. The objective of the current study was to investigate the influence of cortical morphology metrics (i.e. cortical thickness, grey matter volume, cortical area) on age-related BOLD SD changes by treating these cortical morphology metrics as possible physiological confounds using linear mixed models. We studied these metrics in 28 healthy older subjects scanned twice at approximately 2.5 years interval. Results show that BOLD SD is confounded by cortical morphology metrics. Respectively, changes in cortical thickness but not grey matter volume nor cortical area, show a significant interaction with BOLD SD alterations. Our study highlights that cortical thickness changes should be considered when evaluating BOLD SD alternations in the lifespan.